The Effect of Intravitreal Bevacizumab as a Pretreatment of Vitrectomy for Diabetic Vitreous Hemorrhage on Recurrent Hemorrhage. (May 2015) - Berk Ergun, Sule; Toklu, Yasin; Cakmak, Hasan Basri; Raza, Sabri; Simsek, Saban
Abstract Purpose: This study was constructed to compare the rate of rehemorrhage in patients with diabetic vitreous hemorrhage (VH) undergoing pars plana vitrectomy (PPV) with versus without preoperative intravitreal bevacizumab (IVB) injection. Methods: It is a retrospective chart review of all patients who had undergone PPV for diabetic VH from January 2008 to January 2011. Patients who had undergone IVB injection before PPV were assigned to Group 1; the others were assigned to Group 2. Postoperative VH was the main outcome. Results: A total of 65 eyes of 60 patients (19 eyes in Group 1 and 46 eyes in Group 2) were examined. Postoperative VH occured in three eyes (15.8%) in Group 1 and in 13 eyes (28.3%) in Group 2, but this was not statistically significant (p: 0.347). Conclusion: Further studies to evaluate the effect of IVB on postoperative VH are needed.